Kolaborasi Governance dalam Penyusunan Regulasi Desa Tentang Pelindungan Pekerja Migran Indonesia di Kecamatan Ngamprah - Andhani, Dewi; Rachmawati, Emi; Saputra, Ginanjar Wira; Yusri, Amri; Mulyasana, Dedi; Santosa, Pandji; Sarihati, Tati (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2025)
This community service program aimed to build a collaborative multi-stakeholder governance system for Indonesian Migrant Workers (PMI) protection through drafting Village Regulations (Raperdes) in Ngamprah Subdistrict. The main problems addressed were regulatory vacuum, low legal drafting capacity of village officials, absence of PMI data systems, minimal integration of PMI issues in village planning and budgeting, and weak cross-sectoral collaboration. Methods employed included legal drafting training, collaborative workshops, Focus Group Discussions (FGD) with stakeholders, development of manual and digital data templates, and advocacy for PMI issue integration in RKPDes and APBDes. Outputs included: draft PMI Protection Raperdes, training modules, PMI database system, assessment reports, and migrant village collaboration forums. The educational, collaborative, and local regulation-based approach proved effective in enhancing village capacity to protect PMI inclusively and sustainably.